1987
DOI: 10.1139/v87-307
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular rearrangements: Epimerization of bicyclic vinyl tertiary alcohols via a [2,3] sulfoxide sigmatropic rearrangement

Abstract: A general method for inverting the stereochemistry of bicyclic vinyl endo alcohols such as 6 and 12 to give the corresponding exo isomers 10 and 18 is described. The procedures employ a [2,3] sulfoxide rearrangement as a key step. In the case of the norbornene alcohol 12 the intermediate sulfenate ester 13 gives the oxetane 14 rather than the expected sulfoxide 17. It was therefore prepared by thionyl chloride induced rearrangement of 12 to the allylic chloride 15 followed by displacement (PhSNa) and oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Similar transformations have been reported by exo cyclization using electrophilic S and Se reagents to generate oxetanes. The electrophilic addition of PhSe, by use of PhSCl, and etherification was first reported as an unwanted side reaction in the synthesis of a cis -hydrindenone, a bicyclic natural product scaffold . Arjona et al shortly afterward reported electrophilic addition using both PhSCl and PhSeCl with a variety of 7-oxanorbornenic substrates.…”
Section: Synthesis Of Oxetane Derivatives By Intramolecular Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar transformations have been reported by exo cyclization using electrophilic S and Se reagents to generate oxetanes. The electrophilic addition of PhSe, by use of PhSCl, and etherification was first reported as an unwanted side reaction in the synthesis of a cis -hydrindenone, a bicyclic natural product scaffold . Arjona et al shortly afterward reported electrophilic addition using both PhSCl and PhSeCl with a variety of 7-oxanorbornenic substrates.…”
Section: Synthesis Of Oxetane Derivatives By Intramolecular Cyclizationmentioning
confidence: 99%
“…The electrophilic addition of PhSe, by use of PhSCl, and etherification was first reported as an unwanted side reaction in the synthesis of a cis-hydrindenone, a bicyclic natural product scaffold. 220 Arjona et al 221 shortly afterward reported electrophilic addition using both PhSCl and PhSeCl with a variety of 7-oxanorbornenic substrates. The use of PhSCl was more effective at promoting etherification and gave oxetane 168a as the major product, whereas the use of PhSeCl gave the addition of chloride as the major product.…”
Section: Exo Cyclization Of Vinylsilanes Was Later Investigated Bymentioning
confidence: 99%
“…In this context, Brown and Fallis described the epimerization of an endo norbornane alcohol 90 by formation of a sulfenate that rearranged to sulfoxide 91 , producing the target alcohol 92 upon a second rearrangement (Scheme ). The unsaturated norbornene analogue of 91 was prepared by oxidation of the related sulfide and behaved similarly, producing a 9:1 mixture of norbornenols that underwent smooth oxy-Cope rearrangement …”
Section: General Scope Of [23]-sigmatropic Sulfoxide–sulfenate Rearra...mentioning
confidence: 99%
“…The unsaturated norbornene analogue of 91 was prepared by oxidation of the related sulfide and behaved similarly, producing a 9:1 mixture of norbornenols that underwent smooth oxy-Cope rearrangement. 75 Whitham and colleagues reported that the rearrangement of sulfenate 93 afforded a single diastereomer of the sulfoxide, tentatively assigned as 94 (Scheme 18). In contrast, oxidation of the sulfide afforded a 1:1 mixture of allylic sulfoxides 94 and 95.…”
Section: From Allyl Sulfenatesmentioning
confidence: 99%
“…In fact, treatment of 16 with phenylsulfenyl chloride according to the described procedure 19 led to tetracyclic tetrahydrofuran 20 rather than the expected sulfoxide 21 …”
Section: Referencesmentioning
confidence: 99%